Hermeneutics according to Paul Ricouer - Aquino Júnior, Francisco (Argumentos - Revista de Filosofia, 2020)
Paul Ricoeur is one of the most important philosophers of the 20th century and one of the main representatives of modern hermeneutics. His critical-creative dialogue with the history of hermeneutics offers privileged historical-systematic access to the debate about the theoretical status of hermeneutics: Not only resumes the thesis of its most important representatives (historical approach), but, when facing critically with its aporias, it broadens its horizons and inaugurates a new phase in the history of hermeneutics (systematic approach). This work presents in broad lines the reading Ricoeur makes of the history of hermeneutics and its contribution to this debate, seeking to establish, from there, the status quaestionis of the debate on hermeneutics.